Antibacterial Activity of Combined Essential Oils of Cinnamon (Cinnamomum verum) and Tamanu (Calophyllum inophyllum) Against Acne-Causing Bacteria - Sefi Megawati; Meta Safitri; Zahra Huwaida; Diana Sylvia (Jurnal Penelitian Pendidikan IPA, 2025)
Antibacterial agents are microbial metabolism inhibitors that are present in essential oils produced by Cinnamon (Cinnamomum verum) and Tamanu (Calophyllum inophyllum). The objective of this research is to investigate the secondary metabolites and the antibacterial activity of a combination of cinnamon and tamanu essential oils (CTE) against Staphylococcus aureus ATCC 6538 and Staphylococcus epidermidis ATCC 12228. The essential oils of cinnamon and tamanu were analyzed by GC–MS. The combination of the two essential oils was prepared in three different concentrations (1.25, 2.5, and 5%) with five ratios (1:1, 1:2, 1:3, 2:1, and 3:1) for each concentration. The antibacterial test was conducted using the disk diffusion method. The results of the GC–MS analysis showed that the essential oil of cinnamon contained cinnamaldehyde as the main compound (82.59%), while the essential oil of tamanu contained linoleic acid (48.29%). The antibacterial test demonstrated that the CTE at a concentration of 5% in a 3:1 ratio exhibited the highest inhibitory effect against S. aureus ATCC 6538 with an inhibition diameter of 11.25 mm and S. epidermidis ATCC 12228 with an inhibition diameter of 11.25 mm.